2020
DOI: 10.2196/15015
|View full text |Cite
|
Sign up to set email alerts
|

A Lower Leg Physical Activity Intervention for Individuals With Chronic Venous Leg Ulcers: Randomized Controlled Trial

Abstract: Background Individuals with venous leg ulcers (VLUs) suffer disproportionately with multiple chronic conditions, are often physically deconditioned, and demonstrate high levels of physical inactivity. Objective The primary objective of this randomized controlled trial was to establish the feasibility of a mobile health (mHealth) physical activity exercise app for individuals with VLUs to improve lower leg function. Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In contrast, low acceptability, lack of time, health problems, and lack of motivation had a negative impact [ 118 ]. The user characteristic of the female gender positively influenced adherence in a study about an app for a lower leg physical activity intervention for individuals with chronic venous leg ulcers [ 114 ]. Furthermore, in a study on an mHealth app targeting inflammatory bowel disease, it was found that old age, low level of education, and lack of perceived usefulness negatively affected adherence [ 115 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, low acceptability, lack of time, health problems, and lack of motivation had a negative impact [ 118 ]. The user characteristic of the female gender positively influenced adherence in a study about an app for a lower leg physical activity intervention for individuals with chronic venous leg ulcers [ 114 ]. Furthermore, in a study on an mHealth app targeting inflammatory bowel disease, it was found that old age, low level of education, and lack of perceived usefulness negatively affected adherence [ 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…Monetary incentives such as vouchers, lottery tickets, or direct cash contributions were given to participants in 31 of the 97 included primary studies [ 30 , 33 , 44 , 45 , 47 , 48 , 51 , 53 , 56 , 61 , 62 , 64 , 65 , 68 - 72 , 77 , 81 , 88 , 90 , 98 , 101 , 104 - 106 , 108 , 109 , 114 , 116 ]. However, the qualitative synthesis did not yield results regarding the effect of such monetary incentives as an additional intervention component on adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of multi-electrode sensors placed in the dressing was also used to monitor ulcer progression through bioimpedance analysis [ 51 , 52 ]. Some projects focused on physical activity parameters by using footwear-based Bluetooth-enabled triaxial accelerometers paired with mobile phone applications in order to improve lower leg function and strengthen lower extremities in individuals with leg venous ulcers, also recurring to communication functionalities with clinicians [ 53 , 54 ]. Henricson et al (2021) [ 50 ] employed a moisture sensor placed on the patient’s dressings in order to detect moisture concerning the absorbing capacity of the dressings.…”
Section: Resultsmentioning
confidence: 99%
“…Disagreements were resolved through consensus involving the assessment of all four reviewers. The complete list of included articles is presented in the References section [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ].…”
Section: Methodsmentioning
confidence: 99%